Developing Prototype of the Nasu Suwoho Application for Rabies Case Reporting in Endemic Areas, North Sumatera, Indonesia - Tri Bayu Purnama; Yulia Khairina Ashar; Arrafi Insani; Mahin Reza (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Delays in the handling of cases including rabies will affect the severity level caused by the inaccurate handling and detection of cases and tends to be slow. Considering that the era of digital technology is now developing so rapidly, almost all information can be accessed easily today. The purpose of this activity is to provide knowledge or socialization of the plan for a rabies self-reporting program by the community through the Nasu Suwoho application. Community service activities are carried out using a Participatory Action Research approach where the community as the subject and object of this community service activity plays an active role in planning to implement the use of the rabies reporting application. A qualitative approach with in-depth interviews was conducted to the respondents by the research team. Service activities consist of opening, giving material, delivering videos and testing applications. With the Nasu Sowoho application, it is hoped that the signals of rabies cases, humans and animals infected with rabies in the community, health center staff and animal health centers can be properly monitored. This application displays questions in the form of self-diagnosis of the general public about the clinical symptoms of bite cases of rabies-transmitting animals. These clinical symptoms are adapted to general and typical signs that are easily recognized by the public so they can be reported easily. Keyword: Rabies, Digital Health, Qualitative Study